(untitled) (ENTHYMEMA, 2022)
The article analyzes the novel of the modern Russian writer A. Potyomkin Man is canceled (2007), which received a wide public response. The main idea of the work is the need for a radical change of the ‘mass man’ of the turn of the XX-XXI centuries at the psychosomatic level. The ideological and compositional center is the specially built Rimushkino estate in the Oryol province, where the serf spirit of the Russian Empire at the turn of the XVIII-XIX centuries is reproduced. To answer the question of why the estate space of Russia is becoming the most representative field for anthropological experiments of the beginning of the XXI century, we consider the estate neo-myths of the Silver Age (the lost paradise on earth) and the Soviet period (the camp hell living in the mentality), as well as the imperial-colonial concept of the postmodern era (the estate as a frontier in the process of class-oriented internal colonization of the country). The multidimensional semiotics of the estate sets a new relationship between ‘metropolitan’ and ‘provincial’ concerning the other loci of the novel.